Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/asia.201800573
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Lead‐free CsGeI3 Perovskite Colloidal Nanocrystals and Electron Beam‐induced Transformations

Abstract: Colloidal nanocrystals (NCs) of metal halide perovskite have recently aroused great research interest, due to their remarkable optical and electronic properties. We report a solution synthesis of a new member in this category, that is, all-inorganic lead-free cesium germanium iodine (CsGeI ) perovskite NCs. These CsGeI colloidal NCs are confirmed to adopt a rhombohedral structure. Moreover, the electron beam-induced transformations of these lead-free perovskite NCs have been investigated for the first time. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 39 publications
(33 reference statements)
2
85
1
4
Order By: Relevance
“…In contrast to recently reported carboxylate‐capped CsGeI 3 nanocrystals, CsGeI 3 nanocrystals prepared by our method do not – unfortunately – exhibit photoluminescence (PL) emission. However, CsGeBr 3 nanocrystals exhibit a weak PL peak at 500 nm, whose intensity increases with the introduction of cysteNH 3 X, with a highest quantum yield of 0.34%.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…In contrast to recently reported carboxylate‐capped CsGeI 3 nanocrystals, CsGeI 3 nanocrystals prepared by our method do not – unfortunately – exhibit photoluminescence (PL) emission. However, CsGeBr 3 nanocrystals exhibit a weak PL peak at 500 nm, whose intensity increases with the introduction of cysteNH 3 X, with a highest quantum yield of 0.34%.…”
Section: Resultscontrasting
confidence: 93%
“…[51] Metal doping can expand the application of semiconductor nanocrystals by introducing new or modifying existing electronic, optical and magnetic properties. [52][53][54][55] Recently, significant research focused on doping metal halide perovskites with transition or main group metals. [56][57][58] Doping with up to 46% Mn 2 + is currently possible, [59] leading to modified magnetic and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…This decomposition path is a bit different from that of the heavier Pb based MHPs. The aerobic instability of CsGeX 3 perovskites due to the spontaneous oxidation of Ge 2+ to Ge 4+ is a major concern for this materials to find potential applications in optoelectronics …”
Section: Germanium Perovskitesmentioning
confidence: 99%
“…The analogs CsGeX 3 NCs synthesis remained unexplored, probably due to the unfavorable colloidal synthesis procedures. CsGeI 3 NCs were first synthesized by Quan et al by employing modified hot injection synthetic procedure reported by Kovalenko et al [29,58] The controlled precipitation of Cs + , Ge 2 + , I À ions into CsGeI 3 NCs were performed under an inert atmosphere using Schlenk techniques. The rapid injection of a preheated Cs-oleate precursor into Ge(II) iodide solution at 180°C in presence of OLAm, oleic acid (OLAc), and 1-octadecene (1-ODE) solvents produces highly monodispersed cubic NCs ( Figure 2).…”
Section: Germanium Perovskitesmentioning
confidence: 99%
“…Ge‐based halide perovskites possess a formula of AGeX 3 . There has been only one report on CsGeX 3 NCs, that is, CsGeI 3 NCs that crystallize in the rhombohedral structure ( R 3 m ), as depicted in Figure e. CsGeCl 3 and CsGeBr 3 were only explored in their bulk form, which both undergo a pressure‐induced phase transition to a primitive cubic phase at room temperature. Conversely, the CsGeI 3 crystal does not encounter phase transitions during low‐temperature solution growth …”
Section: Crystal Structure Of Lead‐free Halide Perovskite Nanocrystalsmentioning
confidence: 99%